Effects of dose and duration of zinc interventions on risk factors for Type 2 Diabetes and Cardiovascular Disease: A systematic review and meta-analysis - Pompano, Laura M.; Boy, Erick (American Society for Nutrition, 2021)
No meta-analysis has examined the effect of dose and duration of zinc interventions on their impact on risk factors for type 2 diabetes (T2D) or cardiovascular disease (CVD). This study aimed first to compare the effects of zinc interventions dichotomized as low versus high dose (<25 mg/d and ≥25 mg/d, respectively) and short versus long duration (<12 wk and ≥12 wk, respectively) on risk factors for T2D and CVD. Second, it discusses the results from the low-dose and long-duration meta-analyses as a foundation for understanding what impact a zinc-biofortification intervention could have on these risk factors. The PubMed and Cochrane Review databases were searched through January 2020 for full-text, human studies providing zinc supplements (alone) at doses ≤75 mg/d and a placebo. Data on study and sample characteristics and several T2D and CVD risk factors were extracted. There were 1042 and 974 participants receiving zinc and placebo, respectively, from 27 studies. Low-dose zinc supplementation (<25 mg/d) significantly benefited fasting blood glucose, insulin resistance, triglycerides, total cholesterol, and LDL cholesterol. High-dose zinc supplementation (≥25 mg/d) benefited glycated hemoglobin and insulin resistance. Short-duration interventions (<12 wk) benefited fasting blood glucose, insulin resistance, and triglycerides, while long-duration studies (≥12 wk) benefited fasting blood glucose, triglycerides, and total and LDL cholesterol. Effect sizes for low-dose and long-duration interventions were of equal or greater magnitude to those from high-dose or short-duration interventions. Low-dose and long-duration zinc supplementation each improved more risk factors for T2D and CVD than high-dose and short-duration interventions, respectively. It is currently unknown whether low doses of zinc delivered over long durations via a biofortified crop would similarly impact these risk factors. However, this review suggests that low-dose, long-duration zinc intake from supplements, and potentially biofortification, can benefit risk factors for T2D and CVD.